2022
DOI: 10.3389/fcvm.2022.794850
|View full text |Cite
|
Sign up to set email alerts
|

Patients With Bicuspid Aortic Stenosis Undergoing Transcatheter Aortic Valve Replacement: A Systematic Review and Meta-Analysis

Abstract: ObjectiveWe sought to conduct a systematic review and meta-analysis of clinical adverse events in patients undergoing transcatheter aortic valve replacement (TAVR) with bicuspid aortic valve (BAV) vs. tricuspid aortic valve (TAV) anatomy and the efficacy of balloon-expandable (BE) vs. self-expanding (SE) valves in the BAV population. Comparisons aforementioned will be made stratified into early- and new-generation devices. Differences of prosthetic geometry on CT between patients with BAV and TAV were presente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…Now the evidence of TAVI safety and efficacy in TAV anatomy is strong enough [ 1 , 2 ], so one of the suggested study designs is the comparison of TAVI in BAV to TAV. Multiple retrospective studies with and without propensity score matching have been published in a trial to propose such a study and to present more trustable results [ 11 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Now the evidence of TAVI safety and efficacy in TAV anatomy is strong enough [ 1 , 2 ], so one of the suggested study designs is the comparison of TAVI in BAV to TAV. Multiple retrospective studies with and without propensity score matching have been published in a trial to propose such a study and to present more trustable results [ 11 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The bicuspid aortic valve (BAV) is the most common congenital defect with a prevalence ranging between 0.5 and 2.0% [1] and male predominancy (3:1). Classified into three types, according to Sievers [2], the BAV shows geographical variability, with type 1 dominance in Europe/USA and type 0 in China [3]. BAV anatomy frequently coexists with enlarged aortic dimensions [4], and due to the asymmetricity-induced increased wall shear stress confirmed by MRI [5], aortic stenosis or aortopathy may develop at a younger age.…”
Section: Introductionmentioning
confidence: 99%
“…It should be mentioned that early-and new-generation SEV and BEV devices impact safety endpoints in favor of new-generation devices [3]. BAV patients are mainly in the low surgical risk profile due to their younger age.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown promising outcomes of TAVR in patients with bicuspid aortic valves (BAVs), but complications remain a concern [3][4][5][6][7]. BAVs have an elevated risk of procedural complications, because of their anatomical characteristics and the presence of calcium deposits [6,8].…”
Section: Introductionmentioning
confidence: 99%